Barriers to Equity in Cancer Survivorship Care: Perspectives of Cancer Survivors and System Stakeholders - Truant, Tracy L.O. (Glob Qual Nurs Res, 2021)
As more cancer patients survive into post-treatment, the challenge of managing their survivorship care is confronting health care systems globally. In striving to deliver high quality survivorship care, equity constitutes a particularly troublesome challenge. We analyzed accounts from both cancer survivors and stakeholders within care system management to uncover insights with respect to barriers to equitable cancer survivorship services. Beyond the social determinants of health that shape inequities across all of our systems, the cancer care system involves a pattern of prioritizing biomedicine, evidence-based options, and care standardization. We learned that these lead to system rigidities that not only compromise the individualization essential to person-centered care but also obscure the attention to group differences that becomes indispensable to responsiveness to inequities. On the basis of these insights, we reflect on what may be required to begin to redress the current and projected inequities with respect to access to appropriate cancer survivorship supports and services.